Evaluation of homocysteine levels in neonatal calves with diarrhea - Süleyman KOZAT; Cumali ÖZKAN; Eda Nur OKMAN (Kafkas Universitesi Veteriner Fakültesi Dergisi, 2021)
The aim of this study was to investigate the relationship between serum homocysteine (HCY), and creatinine, urea, venous blood gas and electrolytes values in neonatal calves with diarrhea. The study was conducted on a total of 30 calves, 20 with diarrhea and 10 healthy (control), with diarrhea complaints, of diff erent races, sexes and ages ranging from 2-24 days. According to the venous blood gas results, the pCO2 and base deficit values of calves with diarrhea were significantly higher (P<0.001) compared to the control group values, while pH, pO2 and HCO3 values were significantly lower (P<0.001). While serum Na+ and Cl- concentrations in diarrheic calves did not show any statistical change when compared to the control group (P>0.05), serum K+ concentrations were statistically higher (P<0.001). Serum HCY, folate and vitamin B12 concentration values of diarrheic calves were significantly higher (P<0.001) when compared to the control group. As a result; in neonatal calves with diarrhea, it has been concluded that homocystein excretion is disrupted by low renal excretion due to decrease in glomerular filtration rate that caused hyperhomocysteine. In addition, it is thought that this study will shed light on studies that will reveal the eff ect of hyperhomocysteinemia in the cardiovascular system in diarrheic calves.